The Use of Biomarkers in Clinical Management Guidelines: A Critical Appraisal - Esteve-Pastor, María Asunción; Roldán, Vanessa; Rivera-Caravaca, José Miguel; Ramírez-Macías, Inmaculada; Lip, Gregory Y. H.; Marín, Francisco (Thrombosis and Haemostasis, 2019)
In cardiovascular disease (CVD), biomarkers (i.e., “biological markers”) could have multiple roles in understanding the complexity of cardiovascular (CV) pathophysiology and to offer an integrated approach to management. Biomarkers could help in daily practice as a diagnostic tool, to monitor therapy response, to assess prognosis and as early marker of CV damage, or to stratify risk. In recent years, the role of biomarkers in CVD is even more relevant and some have recently been included in clinical management guideline recommendations. The aim of this review is to discuss the recommendations in clinical guidelines of various biomarkers and to review their usefulness in daily clinical practice. Ultimately, a balance is needed between simplicity and practicality for clinical decision-making. Most biomarkers (whether blood, urine, or imaging-based) will improve on clinical risk stratification, but awaiting biomarker results may lead to delays in the initiation of therapy, for example, anticoagulation for stroke prevention in atrial fibrillation. Many biomarkers are nonspecific, being predictive of many CV and non-CV outcomes, so would be better as “rule-out” rather than “rule-in” assessments. Derivation of some biomarkers have also been made in highly selected clinical trial cohorts, where measurement is made at baseline but outcomes determined many years later; given the dynamic nature of risk in the “real world” where patients get older and develop incident risk factors, this may give a false impression of the risk profile. Finally, some laboratory biomarkers have a diurnal variation and inter-/intravariability (and lower limits of detection) in assays, which may be expensive, are added considerations.
Keywords: vascular cell markers; cardiology; management of disease